Continuous carbon fiber composite material and bolt prepared from same
By combining continuous carbon fiber with imidazole epoxy resin and introducing modified polyamide and modified carbon nanotubes into the material, the shortcomings of existing carbon fiber composite bolts in terms of mechanical, heat resistance and aging resistance are solved, and the problem of the bolts in the existing carbon fiber composite material is achieved. Higher performance and longer service life.
Patent Information
- Application Number
- CN202411840408.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing carbon fiber composite bolts cannot meet the requirements of modern industry in terms of mechanical properties, heat resistance and aging resistance.
The method of combining continuous carbon fiber with imidazole epoxy resin is adopted, and the interface compatibility and dispersion of the material are improved through the use of modified polyamide and modified carbon nanotubes, thereby improving the overall performance of the bolts.
Improves the mechanical properties and heat resistance of the bolts, reduces wear, extends service life, and maintains the stability of the connection when temperature changes.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon fiber composite materials, in particular to a continuous carbon fiber composite material and a bolt prepared therefrom. Background Art
[0002] Carbon fiber is a new type of fiber material with high strength, high modulus, high temperature resistance, and the softness and processability of textile fibers. Compared with traditional metal materials, bolts made of fiber composite materials have good lightness and corrosion resistance, and their various properties have certain designability. In particular, carbon fiber reinforced resin-based composite materials have been widely used in modern industrial fields such as aerospace and wind turbine blades due to their excellent performance.
[0003] As the use of carbon fiber composite materials becomes more and more extensive, the market demand for carbon fiber composite threaded fasteners is also increasing; however, with the advancement and development of science and technology, most parts made of carbon fiber composite materials cannot meet people's requirements for parts in terms of mechanical properties, heat resistance and aging resistance.
[0004] In summary, it is of great significance to prepare a bolt made of continuous carbon fiber composite material. Summary of the invention
[0005] The object of the present invention is to provide a continuous carbon fiber composite material and a bolt prepared therefrom, so as to solve the problems raised in the above background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: A continuous carbon fiber composite material, wherein the raw materials of the continuous carbon fiber composite material include the following components: by mass, 20 to 30 parts of imidazole epoxy resin, 55 to 58 parts of continuous carbon fibers, 4 to 6 parts of modified polyamide, 6 to 9 parts of curing agent, and 5 to 7 parts of modified carbon nanotubes.
[0007] The preparation method of the modified carbon nanotubes is more optimized as follows: (1) in a nitrogen atmosphere, β-(acryloyloxy) propionic acid is heated to 80-90° C., 3-chloropropyltriethoxysilane and tetrabutylammonium bromide are added, mixed evenly, reacted for 30-40 minutes, the temperature is reduced to 50° C., sodium hydroxide aqueous solution is added, mixed evenly, reacted for 6-7 hours, cooled to room temperature, purified, and a silane intermediate is obtained; (2) the silane intermediate, 3-mercaptophenylboronic acid, and azobisisobutyronitrile are added to tetrahydrofuran, mixed evenly, incubated at room temperature for 1-2 hours under ultraviolet light, purified, and dried to obtain a silane coupling agent; (3) the carbon nanotubes are added to a 60-70wt% ethanol aqueous solution, ultrasonically dispersed, the silane coupling agent is added, mixed evenly, the temperature is increased to 50-70° C., reacted for 6-8 hours, and the modified carbon nanotubes are obtained.
[0008] More optimally, the raw materials of the silane intermediate include the following components: by mass, 0.4-0.6 parts of β-(acryloyloxy)propionic acid, 8-14 parts of 3-chloropropyltriethoxysilane, 0.04-0.05 parts of tetrabutylammonium bromide, and 2-5 parts of aqueous sodium hydroxide solution; the sodium hydroxide in the aqueous sodium hydroxide solution accounts for 20-28wt%; the mass ratio of the carbon nanotubes to the silane coupling agent is 1:(0.2-0.3).
[0009] The preparation method of the modified polyamide is more optimized as follows: (1) under a nitrogen atmosphere, polyamide is added to deionized water, mixed evenly, methyl thioglycolate is added, reacted at a speed of 600-700 rpm / min for 18-22 hours, purified, and dried to obtain thiolated polyamide; (2) thiolated polyamide, vinyl imidazole, vinyl trimethoxysilane, and azobisisobutyronitrile are added to tetrahydrofuran, mixed evenly, and irradiated under ultraviolet light for 1-2 hours to obtain modified polyamide.
[0010] More optimally, the mass ratio of the polyamide to methyl thioglycolate is 1:(1.3~2); the raw materials of the modified polyamide include the following components: by mass, 0.2~0.3 parts of mercapto polyamide, 1~2 parts of vinyl imidazole, 1.5~3 parts of vinyl trimethoxy silane, 0.002~0.0022 parts of azobisisobutyronitrile, and 20~30 parts of tetrahydrofuran.
[0011] Preferably, the preparation process of the bolt comprises the following steps: Step 1: Add continuous carbon fiber to ethanol aqueous solution, disperse by ultrasonic, add modified polyamide and mix evenly, heat to 60-75°C and stir for 1-2 hours, filter and freeze-dry to obtain raw material A; Step 2: Mix raw material A, imidazole epoxy resin, curing agent and modified carbon nanotubes to obtain a mixture: Step 3: inject the mixed material into the mold, semi-curing it to form a sheet-like film plastic, which is a single layer; Step 4: Cut and stack multiple single layers, and mold them into bolts.
[0012] Preferably, the mass ratio of the continuous carbon fiber to the modified polyamide is 1:(3-4); in the ethanol aqueous solution, the ethanol accounts for 60-70wt%.
[0013] More optimally, the semi-curing temperature is 150-160° C., and the semi-curing time is baking for 5-7 minutes; the compression molding conditions are: temperature of 120-155° C. and pressure of 140-210 MPa.
[0014] Preferably, the average diameter of the continuous carbon fibers is 6-7 μm; the bolts include but are not limited to M5, M6 or M8 hexagonal head bolts, and may be bolts without cotter pin holes.
[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: Continuous carbon fiber has good chemical stability, high strength, and rigidity, so it can withstand higher loads, making bolts more reliable in use; and its relatively low thermal expansion coefficient helps maintain the stability of the connection when the temperature changes. Imidazole epoxy resin has good heat resistance and chemical stability, so that the composite material can still maintain stable performance in high temperature environments; it also has excellent bonding strength and toughness.
[0016] In the scheme, continuous carbon fiber is used as a reinforcing material, and it is combined with imidazole epoxy resin to make a bolt, which can improve the mechanical properties of the bolt. However, the interface compatibility between continuous carbon fiber and imidazole epoxy resin is poor, resulting in reduced mechanical properties of the bolt; therefore, in the scheme, the continuous carbon fiber is modified by modified polyamide, and then mixed with imidazole epoxy resin; wherein, after the polyamide is thiolated, it is reacted with vinyl imidazole and vinyl trimethoxy silane by click chemistry to obtain a modified polyamide; in the scheme, polyamide has self-lubricity and good tolerance, and its friction coefficient is relatively low, which can reduce the friction between the bolt and the mating part, thereby improving the interface shear strength, reducing wear, and extending the service life; and polyamide also has a certain curing effect on imidazole epoxy resin, reducing the amount of curing agent used, so it can enhance the performance of the bolt. The introduction of vinyl trimethoxy silane and vinyl imidazole in polyamide can improve the interface compatibility and dispersibility between continuous carbon fiber and imidazole epoxy resin, so it is beneficial to improve the heat resistance and strength of the bolt.
[0017] In order to further improve the comprehensive performance of the bolts, modified carbon nanotubes are added to the raw materials. The high strength and modulus characteristics of carbon nanotubes can effectively prevent the expansion of cracks in the material. In the scheme, in order to maximize the advantages of carbon nanotubes, they are modified with silane coupling agents. The silane coupling agent is prepared from β-(acryloyloxy) propionic acid, 3-chloropropyltriethoxysilane, and 3-mercaptophenylboric acid.
[0018] In the scheme, β-(acryloyloxy) propionic acid and 3-mercaptophenylboronic acid can promote cross-linking, making the combination between the raw materials tighter, thereby improving the overall thermal stability and mechanical properties. The silane coupling agent improves the dispersibility of carbon nanotubes while enhancing the interface compatibility with epoxy resin, which is beneficial to improving the strength and heat resistance of the bolts. DETAILED DESCRIPTION
[0019] The following is a preferred implementation of the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. For ordinary technicians in this technical field, all other embodiments obtained by ordinary technicians in this field without creative work without departing from the principle of the embodiment of the present invention are within the scope of protection of the present invention.
[0020] In the following specific embodiments, parts are by mass. In this embodiment, it should be noted that the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions, and exemplary examples include: continuous carbon fiber is Japanese Toray T700 model with an average diameter of 7 μm; the model of imidazole epoxy resin is TDE85 / 615; the product number of carbon nanotubes is T19281; the CAS number of benzenesulfonic acid (curing agent) is 98-11-3; the product number of bisphenol A epoxy resin (epoxy resin) is SS9251; the CAS number of triallylamine (epoxy resin curing agent) is 102-70-5; the non-woven fabric is HTS40 F22 12K non-woven fabric; the CAS number of 3-mercaptophenylboric acid is 352526-01-3; the CAS number of 3-chloropropyltriethoxysilane is 5089-70-3; the CAS number of β-(acryloyloxy)propionic acid is 24615-84-7; the CAS number of azobisisobutyronitrile is 78-67-1; the product number of polyamide is XHL0523; the CAS number of methyl thioglycolate is 2365-48-2; the CAS number of vinylimidazole is 1072-63-5; the CAS number of vinyltrimethoxysilane is 2768-02-7.
[0021] The preparation method of modified carbon nanotubes is as follows: (1) in a nitrogen atmosphere, 0.5 parts of β-(acryloyloxy) propionic acid are heated to 80°C, 10 parts of 3-chloropropyltriethoxysilane and 0.04 parts of tetrabutylammonium bromide are added, the mixture is uniformly mixed, and the reaction is carried out for 40 minutes. The temperature is then reduced to 50°C, 4 parts of a 28 wt% aqueous sodium hydroxide solution are added, the mixture is uniformly mixed, and the reaction is carried out for 6 hours. The mixture is cooled to room temperature and purified to obtain a silane intermediate; (2) 7 parts of the silane intermediate and 0.04 parts of tetrabutylammonium bromide are added, the mixture is uniformly mixed, and the reaction is carried out for 40 minutes. 34 parts of 3-mercaptophenylboric acid and 0.002 parts of azobisisobutyronitrile are added to 30 parts of tetrahydrofuran and mixed evenly, incubated under ultraviolet light at room temperature for 2 hours, purified, and dried to obtain a silane coupling agent; (3) carbon nanotubes and silane coupling agent are weighed at a mass ratio of 1:0.25; the carbon nanotubes are added to a 70wt% ethanol aqueous solution, ultrasonically dispersed, the silane coupling agent is added, the mixture is evenly mixed, the temperature is raised to 70°C, and the reaction is performed for 6 hours to obtain modified carbon nanotubes.
[0022] Embodiment 1: A bolt made of a continuous carbon fiber composite material, comprising the following steps: Step 1: The preparation method of the modified polyamide is as follows: (1) polyamide and methyl thioglycolate are weighed in a mass ratio of 1:1.8; under a nitrogen atmosphere, the polyamide is added to deionized water, mixed evenly, methyl thioglycolate is added, reacted at a speed of 700 rpm / min for 22 hours, purified, and dried to obtain a thiolated polyamide; (2) 0.25 parts of thiolated polyamide, 1.5 parts of vinyl imidazole, 2 parts of vinyl trimethoxy silane, and 0.0022 parts of azobisisobutyronitrile are added to 30 parts of tetrahydrofuran, mixed evenly, and irradiated under ultraviolet light for 2 hours to obtain a modified polyamide; 56 parts of continuous carbon fibers were added to an ethanol aqueous solution, ultrasonically dispersed, 6 parts of modified polyamide were added and uniformly mixed, the mixture was heated to 70° C. and stirred for 2 hours, filtered, and freeze-dried to obtain a raw material A; Step 2: uniformly mix the raw material A with 25 parts of imidazole epoxy resin, 8 parts of curing agent, and 5 parts of modified carbon nanotubes to obtain a mixture; Step 3: inject the mixture into the mold and bake it at 150°C for 6 minutes for semi-curing to form a sheet-like film plastic, which is a single layer; Step 4: Cut and stack multiple single layers, and mold them at a temperature of 140° C. and a pressure of 180 MPa to obtain bolts.
[0023] Embodiment 2: A bolt made of a continuous carbon fiber composite material, comprising the following steps: Step 1: The preparation method of the modified polyamide is as follows: (1) polyamide and methyl thioglycolate are weighed in a mass ratio of 1:1.8; under a nitrogen atmosphere, the polyamide is added to deionized water, mixed evenly, methyl thioglycolate is added, reacted at a speed of 700 rpm / min for 22 hours, purified, and dried to obtain a thiolated polyamide; (2) 0.25 parts of thiolated polyamide, 1.5 parts of vinyl imidazole, 2 parts of vinyl trimethoxy silane, and 0.0022 parts of azobisisobutyronitrile are added to 30 parts of tetrahydrofuran, mixed evenly, and irradiated under ultraviolet light for 2 hours to obtain a modified polyamide; 58 parts of continuous carbon fibers were added to an ethanol aqueous solution, ultrasonically dispersed, 6 parts of modified polyamide were added and uniformly mixed, the mixture was heated to 70° C. and stirred for 2 hours, filtered, and freeze-dried to obtain a raw material A; Step 2: uniformly mix the raw material A with 30 parts of imidazole epoxy resin, 8 parts of curing agent, and 7 parts of modified carbon nanotubes to obtain a mixture; Step 3: inject the mixture into the mold and bake it at 150°C for 6 minutes for semi-curing to form a sheet-like film plastic, which is a single layer; Step 4: Cut and stack multiple single layers, and mold them at a temperature of 140° C. and a pressure of 180 MPa to obtain bolts.
[0024] Embodiment 3: A bolt made of a continuous carbon fiber composite material, comprising the following steps: Step 1: The preparation method of the modified polyamide is as follows: (1) polyamide and methyl thioglycolate are weighed in a mass ratio of 1:1.8; under a nitrogen atmosphere, the polyamide is added to deionized water, mixed evenly, methyl thioglycolate is added, reacted at a speed of 700 rpm / min for 22 hours, purified, and dried to obtain a thiolated polyamide; (2) 0.25 parts of thiolated polyamide, 1.5 parts of vinyl imidazole, 2 parts of vinyl trimethoxy silane, and 0.0022 parts of azobisisobutyronitrile are added to 30 parts of tetrahydrofuran, mixed evenly, and irradiated under ultraviolet light for 2 hours to obtain a modified polyamide; 55 parts of continuous carbon fibers were added to an ethanol aqueous solution, ultrasonically dispersed, 6 parts of modified polyamide were added and uniformly mixed, the mixture was heated to 70° C. and stirred for 2 hours, filtered, and freeze-dried to obtain a raw material A; Step 2: uniformly mix the raw material A with 20 parts of imidazole epoxy resin, 5 parts of curing agent, and 7 parts of modified carbon nanotubes to obtain a mixture; Step 3: inject the mixture into the mold and bake it at 150°C for 6 minutes for semi-curing to form a sheet-like film plastic, which is a single layer; Step 4: Cut and stack multiple single layers, and mold them at a temperature of 140° C. and a pressure of 180 MPa to obtain bolts.
[0025] Comparative Example 1 is based on Example 2, but without the addition of modified polyamide; Step 1: Evenly mix 58 parts of continuous carbon fibers, 30 parts of imidazole epoxy resin, 8 parts of curing agent, and 7 parts of modified carbon nanotubes to obtain a mixture; Step 2: inject the mixture into the mold and bake it at 150°C for 6 minutes for semi-curing to form a sheet-like film plastic, which is a single layer; Step 3: Cut and stack multiple single layers, and mold them at a temperature of 140° C. and a pressure of 180 MPa to obtain bolts.
[0026] Comparative Example 2 is based on Example 2, but modified carbon nanotubes are not added to the slurry; Step 1: The preparation method of the modified polyamide is as follows: (1) polyamide and methyl thioglycolate are weighed in a mass ratio of 1:1.8; under a nitrogen atmosphere, the polyamide is added to deionized water, mixed evenly, methyl thioglycolate is added, reacted at a speed of 700 rpm / min for 22 hours, purified, and dried to obtain a thiolated polyamide; (2) 0.25 parts of thiolated polyamide, 1.5 parts of vinyl imidazole, 2 parts of vinyl trimethoxy silane, and 0.0022 parts of azobisisobutyronitrile are added to 30 parts of tetrahydrofuran, mixed evenly, and irradiated under ultraviolet light for 2 hours to obtain a modified polyamide; 58 parts of continuous carbon fibers were added to an ethanol aqueous solution, ultrasonically dispersed, 6 parts of modified polyamide were added and uniformly mixed, the mixture was heated to 70° C. and stirred for 2 hours, filtered, and freeze-dried to obtain a raw material A; Step 2: Mix raw material A with 30 parts of imidazole epoxy resin and 8 parts of curing agent to obtain a mixture; Step 3: inject the mixture into the mold and bake it at 150°C for 6 minutes for semi-curing to form a sheet-like film plastic, which is a single layer; Step 4: Cut and stack multiple single layers, and mold them at a temperature of 140° C. and a pressure of 180 MPa to obtain bolts.
[0027] Comparative Example 3 Based on Example 2, the carbon nanotubes were modified using a conventional silane coupling agent; Step 1: The preparation method of the modified polyamide is as follows: (1) polyamide and methyl thioglycolate are weighed in a mass ratio of 1:1.8; under a nitrogen atmosphere, the polyamide is added to deionized water, mixed evenly, methyl thioglycolate is added, reacted at a speed of 700 rpm / min for 22 hours, purified, and dried to obtain a thiolated polyamide; (2) 0.25 parts of thiolated polyamide, 1.5 parts of vinyl imidazole, 2 parts of vinyl trimethoxy silane, and 0.0022 parts of azobisisobutyronitrile are added to 30 parts of tetrahydrofuran, mixed evenly, and irradiated under ultraviolet light for 2 hours to obtain a modified polyamide; 58 parts of continuous carbon fibers were added to an ethanol aqueous solution, ultrasonically dispersed, 6 parts of modified polyamide were added and uniformly mixed, the mixture was heated to 70° C. and stirred for 2 hours, filtered, and freeze-dried to obtain a raw material A; Step 2: The preparation method of modified carbon nanotubes is as follows: carbon nanotubes and 3-aminopropyltriethoxysilane are weighed in a mass ratio of 1:0.25; the carbon nanotubes are added to a 70wt% ethanol aqueous solution, ultrasonically dispersed, 3-aminopropyltriethoxysilane is added, uniformly mixed, heated to 70°C, reacted for 6 hours, and modified carbon nanotubes are obtained; The raw material A is mixed evenly with 30 parts of imidazole epoxy resin, 8 parts of curing agent, and 7 parts of modified carbon nanotubes to obtain a mixture; Step 3: inject the mixture into the mold and bake it at 150°C for 6 minutes for semi-curing to form a sheet-like film plastic, which is a single layer; Step 4: Cut and stack multiple single layers, and mold them at a temperature of 140° C. and a pressure of 180 MPa to obtain bolts.
[0028] Comparative Example 4 is based on Example 2, but the amount of modified carbon nanotubes is increased; Step 1: The preparation method of the modified polyamide is as follows: (1) polyamide and methyl thioglycolate are weighed in a mass ratio of 1:1.8; under a nitrogen atmosphere, the polyamide is added to deionized water, mixed evenly, methyl thioglycolate is added, reacted at a speed of 700 rpm / min for 22 hours, purified, and dried to obtain a thiolated polyamide; (2) 0.25 parts of thiolated polyamide, 1.5 parts of vinyl imidazole, 2 parts of vinyl trimethoxy silane, and 0.0022 parts of azobisisobutyronitrile are added to 30 parts of tetrahydrofuran, mixed evenly, and irradiated under ultraviolet light for 2 hours to obtain a modified polyamide; 58 parts of continuous carbon fibers were added to an ethanol aqueous solution, ultrasonically dispersed, 6 parts of modified polyamide were added and uniformly mixed, the mixture was heated to 70° C. and stirred for 2 hours, filtered, and freeze-dried to obtain a raw material A; Step 2: uniformly mix the raw material A with 30 parts of imidazole epoxy resin, 8 parts of curing agent, and 20 parts of modified carbon nanotubes to obtain a mixture; Step 3: inject the mixture into the mold and bake it at 150°C for 6 minutes for semi-curing to form a sheet-like film plastic, which is a single layer; Step 4: Cut and stack multiple single layers, and mold them at a temperature of 140° C. and a pressure of 180 MPa to obtain bolts.
[0029] Comparative Example 5 is based on Example 2, but without adding modified polyamide and modified carbon nanotubes; Step 1: Evenly mix 58 parts of continuous carbon fiber, 30 parts of imidazole epoxy resin and 8 parts of curing agent to obtain a mixture; Step 2: inject the mixture into the mold and bake it at 150°C for 6 minutes for semi-curing to form a sheet-like film plastic, which is a single layer; Step 3: Cut and stack multiple single layers, and mold them at a temperature of 140° C. and a pressure of 180 MPa to obtain bolts.
[0030] Testing experiment: 7 bolts of each of Examples 1 to 3 and Comparative Examples 1 to 5 were placed in hot air at 80°C for aging test for 4 days; the interface shear strength of the bolts of Examples 1 to 3 and Comparative Examples 1 to 5 before and after aging was tested using a LE055 (100kN) universal testing machine; and the decrease rate of the interface shear strength before and after aging was calculated;
[0031] Table 1 Conclusion: Comparative Example 1 is based on Example 2, but modified polyamide is not added; the performance of the bolt after the aging test is reduced, because polyamide has a certain heat resistance, and the modified polyamide modifies carbon nanotubes, which can improve the interface bonding force between carbon nanotubes and other raw materials. Comparative Example 2 is based on Example 2, but modified carbon nanotubes are not added to the slurry; Comparative Example 3 is based on Example 2, and carbon nanotubes are modified with conventional silane coupling agents; the performance of the bolt after the aging test is reduced; because β-(acryloyloxy) propionic acid and 3-mercaptophenylboronic acid can promote crosslinking, making the bonding between the raw materials tighter, which is beneficial to improve the thermal stability and mechanical properties of the bolt. Comparative Example 4 is based on Example 2, and the amount of modified carbon nanotubes is increased; the dispersion of carbon nanotubes in it is reduced, and its reinforcing effect cannot be fully exerted, which leads to the performance of the bolt. Comparative Example 5 is based on Example 2, but modified polyamide and modified carbon nanotubes are not added; therefore, the performance of the bolt after the aging test is reduced.
[0032] Finally, it should be noted that the above is only a preferred embodiment of the present invention, but the protection scope of this application is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the spirit and principle of the present invention and within the technical scope disclosed in this application should be included in the protection scope of this application; in the absence of conflict, the embodiments of this application and the features in the embodiments can be combined with each other. Therefore, the protection scope of this application shall be based on the protection scope of the claims.
Claims
1. A continuous carbon fiber composite material, characterized in that: The raw materials of the continuous carbon fiber composite material include the following components: by mass, 20 to 30 parts of imidazole epoxy resin, 55 to 58 parts of continuous carbon fibers, 4 to 6 parts of modified polyamide, 6 to 9 parts of curing agent, and 5 to 7 parts of modified carbon nanotubes.
2. The continuous carbon fiber composite material according to claim 1, characterized in that: The preparation method of the modified carbon nanotubes is as follows: (1) in a nitrogen atmosphere, β-(acryloyloxy) propionic acid is heated to 80-90° C., 3-chloropropyltriethoxysilane and tetrabutylammonium bromide are added, the mixture is uniformly mixed, and the mixture is reacted for 30-40 minutes. The temperature is then reduced to 50° C., an aqueous sodium hydroxide solution is added, the mixture is uniformly mixed, the mixture is reacted for 6-7 hours, the mixture is cooled to room temperature, and the mixture is purified to obtain a silane intermediate; (2) the silane intermediate, 3-mercaptophenylboronic acid, and azobisisobutyronitrile are added to tetrahydrofuran, the mixture is uniformly mixed, the mixture is incubated at room temperature under an ultraviolet lamp for 1-2 hours, the mixture is purified, and the mixture is dried to obtain a silane coupling agent; (3) the carbon nanotubes are added to a 60-70wt% ethanol aqueous solution, the mixture is ultrasonically dispersed, the silane coupling agent is added, the mixture is uniformly mixed, the temperature is increased to 50-70° C., and the mixture is reacted for 6-8 hours to obtain a modified carbon nanotube.
3. The bolt made of continuous carbon fiber composite material according to claim 2, characterized in that: The raw materials of the silane intermediate include the following components: by mass, 0.4-0.6 parts of β-(acryloyloxy) propionic acid, 8-14 parts of 3-chloropropyltriethoxysilane, 0.04-0.05 parts of tetrabutylammonium bromide, and 2-5 parts of sodium hydroxide aqueous solution; the sodium hydroxide in the sodium hydroxide aqueous solution accounts for 20-28wt%; the mass ratio of the carbon nanotubes to the silane coupling agent is 1:(0.2-0.3).
4. The continuous carbon fiber composite material according to claim 1, characterized in that: The preparation method of the modified polyamide is as follows: (1) in a nitrogen atmosphere, adding polyamide to deionized water, mixing uniformly, adding methyl thioglycolate, reacting at a speed of 600-700 rpm / min for 18-22 hours, purifying, and drying to obtain thiolated polyamide; (2) adding thiolated polyamide, vinyl imidazole, vinyl trimethoxysilane, and azobisisobutyronitrile to tetrahydrofuran, mixing uniformly, and irradiating under ultraviolet light for 1-2 hours to obtain modified polyamide.
5. The continuous carbon fiber composite material according to claim 1, characterized in that: The mass ratio of the polyamide to methyl thioglycolate is 1:(1.3-2); the raw materials of the modified polyamide include the following components: by mass, 0.2-0.3 parts of mercapto polyamide, 1-2 parts of vinyl imidazole, 1.5-3 parts of vinyl trimethoxy silane, 0.002-0.0022 parts of azobisisobutyronitrile, and 20-30 parts of tetrahydrofuran.
6. The bolt made of continuous carbon fiber composite material according to claim 1, characterized in that: The preparation process of the bolt comprises the following steps: Step 1: Add continuous carbon fiber to ethanol aqueous solution, disperse by ultrasonic, add modified polyamide and mix evenly, heat to 60-75°C and stir for 1-2 hours, filter and freeze-dry to obtain raw material A; Step 2: Mix raw material A, imidazole epoxy resin, curing agent and modified carbon nanotubes to obtain a mixture: Step 3: inject the mixed material into the mold, semi-curing it to form a sheet-like film plastic, which is a single layer; Step 4: Cut and stack multiple single layers, and mold them into bolts.
7. The bolt made of continuous carbon fiber composite material according to claim 6, characterized in that: The mass ratio of the continuous carbon fiber to the modified polyamide is 1:(3-4); in the ethanol aqueous solution, the ethanol accounts for 60-70wt%.
8. The bolt made of continuous carbon fiber composite material according to claim 6, characterized in that: The semi-curing temperature is 150-160° C., and the semi-curing time is baking for 5-7 minutes; the compression molding conditions are: temperature of 120-155° C. and pressure of 140-210 MPa.
9. The bolt made of continuous carbon fiber composite material according to claim 6, characterized in that: The average diameter of the continuous carbon fibers is 6-7 μm; the bolts include M5, M6 or M8 hexagonal head bolts.
Citation Information
Patent Citations
Fishing rod capable of preventing coating peeling and preparation method of fishing rod
CN105061992A
Corrosion-resistant and wear-resistant epoxy coating and preparation method thereof
CN118027779A
Integrally-formed all-carbon fiber hub and manufacturing process
CN118271793A
Epoxy resin composition, prepreg, and method for producing fiber-reinforced composite material
JP2017122205A
Manufacturing method of continuous carbon fiber-reinforced composite materials and manufacturing method of composite formed article
KR1020180020541A